Latar Belakang Sosial Berdirinya Lembaga Pendidikan Islam Terpadu di Indonesia - Frimayanti, Ade Imelda (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
He rises of a unified Islamic schools seem to be the meeting point of the various needs of the community, such as the desire to have a school that is not only high academic quality, but it also has depth in diversity. Therefore, there are some things behind the rise of Islamic educational institutions integrated sociologically, the education system is one form of reaction of the schools to the demands of globalization, among other crises noble character, the business of parents, community needs for schools excel, public awareness of the importance of education integrated, public perception of the quality of Islamic education, education orientation are cognitive and dichotomy of education in Indonesia. Through integrated Islamic education institutions are expected to prepare a generation of Muslims who are able to answer and face the challenges of the times.